Pengenalan Teknik Komputer bagi Siswa SMAK 4 BPK Penabur Jakarta - Wijaya, Marvin Chandra; Yapinus, Pin Panji; Loekito, Jimmy Agustian; Tanubrata, Markus; Lehman, Andrew Sebastian; Cheol, Shin Min; Wong, Karenina (Penerbit Goodwood, 2024)
Purpose: This service provides knowledge in the field of computer engineering. The computer engineering knowledge provided consisted of an introduction to computer systems, multimedia, and computer-controlled equipment. The participants in this service were the SMAK 4 BPK Penabur Jakarta. Methodology/approach: The method consists of four activity steps: coordination, preparation, implementation, evaluation, and report preparation. The coordination stage was performed to equalize the perceptions of the training activity material. The preparatory stage was performed to create training materials and prepare the equipment. The training participants were given material directly in the laboratory and the results of the activity were evaluated. Results/findings: The participants gained knowledge in the fields of computer systems, multimedia, and computer-controlled equipment. The results of the service evaluation tested on the participants showed that this activity was successful in improving the participants' abilities in the field of computer engineering. Limitations: Due to limited teaching time, the learning of materials was not in-depth and detailed. The teaching materials provided were limited to the initial introductory stage. Contribution: This introduction to the field of computer engineering has been provided to improve participants' abilities or insights in the field of computer technology. The learning material provided was computer technology, an introduction to technology in the multimedia field, and an introduction to computer-controlled hardware. The results of the evaluation showed that 100% of the training participants were able to absorb the material provided in this activity. The understanding gained can contribute to participants being able to choose a higher education that suits their interests.